Z-isomerization of retinoids through combination of monochromatic photoisomerization and metal catalysis. Issue 35 (28th August 2019) - Kahremany, Shirin; Sander, Christopher Lane; Tochtrop, Gregory P.; Kubas, Adam; Palczewski, Krzysztof
Abstract : Photoisomerization of therapeutic cis -retinoids using monochromatic UV light-tunable via photocatalysts and explained by DFT calculations. Abstract : Catalytic Z -isomerization of retinoids to their thermodynamically less stable Z -isomer remains a challenge. In this report, we present a photochemical approach for the catalytic Z -isomerization of retinoids using monochromatic wavelength UV irradiation treatment. We have developed a straightforward approach for the synthesis of Z -retinoids in high yield, overcoming common obstacles normally associated with their synthesis. Calculations based on density functional theory (DFT) have allowed us to correlate the experimentally observed Z -isomer distribution of retinoids with the energies of chemically important intermediates, which include ground- and excited-state potential energy surfaces. We also demonstrate the application of the current method by synthesizing gram-scale quantities of 9- cis -retinyl acetate9 Z -a . Operational simplicity and gram-scale ability make this chemistry a very practical solution to the problem of Z -isomer retinoid synthesis.